Wrocławskie Towarzystwo Opieki nad Więźniami. 25 lat działalności - Szablicka-Żak, Jolanta (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2016)
The Wrocław Society for Prisoners’ Aid (WSPA) is a voluntary, self-governing non-governmental organization active since 1989. The Society brings together people who are will-ing to provide legal, material and non-material assistance to prisoners and their families. In 1999, the WSPA launched the autonomous Lower Silesia Mediation Center, which aims to promote restorative justice and family mediation. The WSPA is governed by its Statute and conducts its activities in the following areas: penal, post-penitentiary, educational, charitable as well as mediation activities at detention facilities in Wroclaw and Wołów. The WSPA/Lower Silesia Mediation Center is one of the few non-governmental organizations with extensive experience of successfully operating in Wrocław, or in Poland for that matter, even though assistance to prisoners does not enjoy considerable support in the Polish society.
Keywords: Wrocławskie Towarzystwo Opieki nad Więźniami; Dolnośląski Ośrodek Mediacji; prawa człowieka; organizacja pozarządowa; mediacja